Disentangling the effects of host relatedness and elevation on haemosporidian parasite turnover in a clade of songbirds. Issue 5 (19th May 2021) - Starkloff, Naima C.; Turner, Wendy C.; FitzGerald, Alyssa M.; Oftedal, Michelle C.; Martinsen, Ellen S.; Kirchman, Jeremy J.
Abstract: The persistence of a parasite species in an ecological community is determined both by its environmental tolerance and host breadth. The relative contribution of these niche characteristics to parasite community structure is challenging to parse because host persistence is also a consequence of extrinsic environmental factors. We investigated haemosporidian parasites (genera Plasmodium, Leucocytozoon, and Haemoproteus ) in a clade of avian hosts in eastern North America. Species in this clade of Catharus thrushes occupy specific elevational bands in a non‐phylogenetically determined manner. This allowed us to tease apart the effects of host relatedness and elevation on parasite community structure, diversity, and infection prevalence. We screened blood and tissue samples from 414 adult birds from four mountain ranges in the Appalachian Highlands for blood parasites using a cytochrome‐ b ‐nested PCR protocol and identified parasite lineages by sequencing. We found an overall infection prevalence of 88.4% and identified a total of 38 parasite lineages including six novel lineages. Parasite community patterns varied by genus. Host relatedness rather than elevational zone predicted the beta turnover and phylobeta turnover of Leucocytozoon parasites, indicating that closely related rather than geographically proximate host species had more similar parasites. This pattern was not seen in Plasmodium parasites because the diversity of this parasite genus varied considerably in the high elevational zones among mountain ranges, that is, a sky‐island effect. Haemoproteus parasites were rare in this study system. Our study suggests that the mechanisms that underlie community structuring vary between haemosporidian genera due to differences in the degree of host sharing among lineages.